Effectiveness of 10% and 15% Red Betel Leaf Extract (Piper Crocatum) Against Enterococcus Faecalis as an Antibacterial Agent in Root Canal Treatment - Maya Sari Dewi; I Gusti Ngurah Bagus Tista; Daniel Bhernath Senduk (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Enterococcus faecalis is a major cause of root canal treatment failure due to its resistance to conventional medicaments such as calcium hydroxide. This study aimed to evaluate the antibacterial effect of red betel leaf (Piper crocatum) extract at concentrations of 10% and 15% against E. faecalis. Materials and Methods: A true experimental design with a post-test only control group was used. Samples were divided into four groups: Piper crocatum 10% and 15%, positive control (10% Ca(OH)₂), and negative control (sterile aquadest). Antibacterial activity was tested using the agar diffusion method, measuring inhibition zone diameters. Data were analyzed with one-way ANOVA followed by Tukey’s test. Results and Discussions: The results showed that both concentrations inhibited E. faecalis, with 15% producing greater inhibition than 10%, while Ca(OH)₂ remained the most effective. Conclusion: It can be concluded that Piper crocatum extract over 10% percentage has potential as a herbal alternative for intracanal medicament in root canal therapy.